Effect of CES1 genetic variation on enalapril steady‐state pharmacokinetics and pharmacodynamics in healthy subjects. Issue 12 (26th May 2021) - Her, Lucy H.; Wang, Xinwen; Shi, Jian; Choi, Hee Jae; Jung, Sun Min; Smith, Logan S.; Wu, Audrey H.; Bleske, Barry E.; Zhu, Hao‐Jie
Abstract : Aims: Enalapril is a prodrug and needs to be activated by carboxylesterase 1 (CES1). A previous in vitro study demonstrated the CES1 genetic variant, G143E (rs71647871), significantly impaired enalapril activation. Two previous clinical studies examined the impact of G143E on single‐dose enalapril PK (10 mg); however, the results were inconclusive. A prospective, multi‐dose, pharmacokinetics and pharmacodynamics (PK/PD) study was conducted to determine the impact of the CES1 G143E variant on enalapril steady‐state PK and PD in healthy volunteers. Methods: Study participants were stratified to G143E non‐carriers ( n  = 15) and G143E carriers ( n  = 6). All the carriers were G143E heterozygotes. Study subjects received enalapril 10 mg daily for seven consecutive days prior to a 72 hour PK/PD study. Plasma concentrations of enalapril and its active metabolite enalaprilat were quantified by an established liquid chromatography–tandem mass spectrometry (LC–MS/MS) method. Results: The CES1 G143E carriers had 30.9% lower enalaprilat C max ( P  =  0.03) compared to the non‐carriers (38.01 vs . 55.01 ng/mL). The carrier group had 27.5% lower AUC0–∞ ( P  =  0.02) of plasma enalaprilat compared to the non‐carriers (374.29 vs . 515.91 ng*h/mL). The carriers also had a 32.3% lower enalaprilat‐to‐enalapril AUC0–∞ ratio ( P  =  0.003) relative to the non‐carriers. The average maximum reduction of systolic blood pressure in the non‐carrier group was approximately 12.4% at the end of the study compared to the baseline ( P  =  0.001). No statistically significant blood pressure reduction was observed in the G143E carriers. Conclusions: The CES1 loss‐of‐function G143E variant significantly impaired enalapril activation and its systolic blood pressure‐lowering effect in healthy volunteers.